Oblicz wartość liczbową wyrażenia:
a) -y+8x-z-2x dla x=-2 y=6 z=-3
b)-8y-4z+x-y-2z+1 dla x=-0,5 y=-1 z=2
c)9y-(7y+x)+(6x-7y) dla x=-2 y=3
d) (6a-8b-0,7)-(6,9+a-5b)+1,8 dla a=0,2 b=0,1
e) ¹₂abc-(-4ab+2abc)+(-bc+5ab) dla a=-2 b=¹₂ c=-4
Z obliczeniami proszę ;)

1

Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-17T19:49:59+01:00
A) -y+8x-z-2x=6x-y-z=6*(-2)-6+3=-12-6+3=-15

b)-8y-4z+x-y-2z+1=-7y-6z+x+1=-7*(-1)-6*2-0,5+1=7-12-0,5+1=-4,5

c)9y-(7y+x)+(6x-7y)=9y-7y-x+6x-7y=-5y+5x=-5*3+5*(-2)=-15-10=-25

d) (6a-8b-0,7)-(6,9+a-5b)+1,8=6a-8b-0,7-6,9-a+5b=-5a-3b-7,6=-5*0,2-3*0,1-7,6=-1-0,3-7,6=-8,9

e) ¹₂abc-(-4ab+2abc)+(-bc+5ab)=½abc+4ab-2abc-bc+5ab= -1½abc+9ab-bc=-3/2*(-2)*½*(-4)+9*(-2)*½-½*4=-2-9-2=-13